DYNAMICS OF PERSONALITY IN THE CHARACTER OF AMY DUNNE IN DAVID FINCHER’S MOVIE GONE GIRL - Rachmadany, Erie Putri (LANTERN (Journal on English Language, Culture and Literature), 2016)
Gone Girl is a movie about murder directed by David Fincher. The purpose of this essay is to analyze the main character’s personality through her behavior by discussing intrinsic and extrinsic aspects in this movie. The focus of this essay is Amy Dunne’s dynamics. In order to figure this out, the writer uses psychoanalysis approach by using Sigmund Freud’s theory on the dynamics of personality. From this analysis, it can be concluded that Amy Dunne’s dynamics is leaning on her id which makes her personality unstable.